Analysis of the relationship between the level of corruption, economic growth and the quality of life of the population (on the example of individual countries of the world) - I. E. Digel; Zh. G. Imangali; E. I. Borisova (Экономика: стратегия и практика, 2021)
The difficulty of conducting an empirical assessment of the true extent of corruption, caused by the lack of the necessary data, has contributed to the emergence of a new round of research focusing on the study of the influence of various factors on corruption. At the same time, such studies are distinguished by a variety of approaches to the choice of indicators and objects of study, as well as by the difference, and sometimes contradictory conclusions. These circumstances actualize the research topic. The purpose of the article to determine the relationship between corruption, economic growth and the quality of life of the population in five countries of the world, representing different parts of the world and geo-economics regions. The hypothesis of the study is the assertion that for developed countries the correlation between perceptions of corruption and indicators will be lower than for developing countries. The objects of research are Kazakhstan, Russia, Germany, USA and Finland. The subject of the research the relationship between the level of corruption, economic growth and the quality of life of the population. The study uses statistical research methods. The initial data of the study were the reports of Transparency International on the Corruption Perceptions Index, UNDP on the Human Development Index, as well as official data from the state statistical services of the countries in question.In the course of the work, the boundaries of the interpretation of the term “corruption” were determined, the relevance of the study of the relationship between corruption, GDP per capita and the quality of life was briefly described, and a correlation analysis was carried out between the indicators. The results of the study represent conclusions about the quality and strength of the relationship between corruption, economic growth and the quality of life of the population. The scientific contribution of the research is to substantiate possible directions for improving research to establish the relationship between corruption and other socio-economic indicators. The practical significance of the study lies in the presentation of the evidence base for the fact that the relationship of the studied indicators may be different in different countries. The direction for future research is the possibility of using the assessment methodology for other groups of countries.